Mobility test protocols for the elderly: a methodological note - Nejc Sarabon; Stefan Löfler; Gabriella Hosszu; Christian Hofer (PAGEPress Publications, 2015)
Consequences of falls are a major health problem in elderly. Poor balance is the precursor of falls and balance impairment has been evidenced after an injury. On the other hand, balance and stability can be improved with training. At the beginning of the project Mobility in Aging one of the questions was how to measure dynamic and static balance in order to get reliable and sensitive parameters to follow the effect of decay in movement functions in elderly or to track the improvement after training. In this short report we will give a couple of answers to a long standing debate. There is indeed evidence in literature that stability and balance is very important. Elderly people often shift from the so called ankle strategy to the hip strategy for balancing. The reflex reactions are the more to decay and we observed more co-contractions. Also, inactivity causes slower muscles contractions. Our goal should be a combination of trainings, where we can see changes at neuromuscular, structural and molecular levels, but we would like to say that our training protocols did not touch all the aspects of movement function we aimed to observe. Future projects will hopefully provide the missing information.